2001
DOI: 10.1149/1.1386916
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Moisture Resistance of Siloxane-Based Low-Dielectric-Constant Materials

Abstract: Resistance of siloxane-based, low-dielectric-constant ͑low-k͒ dielectrics against heat and moisture stress is clarified. The organosilica-glass ͑OSG͒ and the silicon-oxycarbide are shown to be the most reliable: the k-values are stable even after a heating test at 650°C and a pressure cooker treatment for 100 h. This stability is high enough to ensure the low-k property throughout fabricating multilevel interconnects and long-term reliability after the fabrication. This is shown to be due to the stability of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…It has been reported that lowering the discharge power density decreases the dielectric constant of SiO͑C,H͒ films. 13,14 An increase in the process pressure produces the same effect as seen from our results. This similarity is understandable, as lower discharge power density or higher pressure ͑leading to reduced mean free path of the species͒ both lower the degree of dissociation of the radicals 15,16 and result in an increased incorporation of Si-͑CH 3 ͒ m group in the films.…”
Section: Resultssupporting
confidence: 89%
“…It has been reported that lowering the discharge power density decreases the dielectric constant of SiO͑C,H͒ films. 13,14 An increase in the process pressure produces the same effect as seen from our results. This similarity is understandable, as lower discharge power density or higher pressure ͑leading to reduced mean free path of the species͒ both lower the degree of dissociation of the radicals 15,16 and result in an increased incorporation of Si-͑CH 3 ͒ m group in the films.…”
Section: Resultssupporting
confidence: 89%
“…For the moisture reliability test, the as cured as well as the HWGAH treated HSQ films were immersed in water at 80 -C for 3 h in a closed beaker (container). These conditions were chosen for accelerated testing and are similar to the pressure cooker test (PCT) in an earlier study [6]. The chemical structure of the cured HSQ films before and after the hot wire and water treatment was investigated by Fourier transform infrared (FTIR) spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…These results demonstrate that ͑1͒ oxidizing chemistries and reducing chemistries with nitrogen transform the porous SiOCH film in an hydrophilic film, while ͑2͒ nitrogen-free reducing chemistries maintain the hydrophobic properties of the porous SiOCH material. Previous studies [22][23][24][25][26] have shown that in oxidizing plasmas oxygen reactive species can deeply diffuse into the film through the pores and react with methyl groups producing Si-OH bonds leading to moisture uptake. In the case of reducing plasmas with nitrogen, 24-26 hydrogen reactive species ͑NH x ,H͒ can react with Si-O-Si and Si-CH 3 to form Si-NH 2 and Si-OH terminating bonds which can also lead to moisture uptake.…”
Section: Discussionmentioning
confidence: 99%